Partisipasi Masyarakat dalam Pengelolaan Community Based Tourism di Desa Wisata Waturaka, Kabupaten Ende - Rudolfus Sawu, Michael; Pramita Sugiarti, Dian (JURNAL DESTINASI PARIWISATA; Vol 8 No 1 (2020): VOL 8, NO 1 (2020): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2020)
Waturaka Tourism Village is a community-based development. Waturaka tourism village has a wealth of natural resource assets and also a very massive culture. Therefore, managing elements of tourism products through the concept of “community based tourism” is ideal in an effort to provide economic benefits for local communities, nature and cultural conservation amid the rampant negative conventional mass tourism. This study aims to look at the components of tourism planning and community participation in it to produce philosophical implementation of community-based tourism.Technique used to collect the data in this research is observation, interview as well as literature study. Descriptive qualitative is used as the data analysis technique in this research. The results of this study indicate that, the management of the tourism product component in Waturaka tourism village was managed by community with a very high level of participation (citizen power) on one hand but not on the other. It is because the motive of local people's enthusiasm to develop community-based tourism in terms of awareness of global reality. Suggestions from this research are tourism awareness groups ( Kelompok sadar wisata) are expected to build networks with external parties in the context of the tourism village marketing, the government and non-government organization is expected to continue to empower local communities so as to produce massive competence in the tourism industry in order to provide maximum satisfaction to tourists. Keywords: CBT, tourism village, participation